High-intensity actions in elite soccer: Current status and future perspectives - Filter, A.; Olivares-Jabalera, J.; Dos'Santos, T.; Madruga, M.; Lozano, J. M. O.; Molina, A.; Santalla, A.; Requena, B.; Loturco, I. (International Journal of Sports Medicine, 2023)
Over the years, soccer has become more physically demanding; the number and frequency of high-intensity actions have increased, and these activities are decisive in determining the match outcome. Importantly, the reductionist approach commonly used to analyze high-intensity actions does not contemplate a more contextualized perspective on soccer performance. Traditionally, most investigations have only provided quantitative data regarding sprints (i. e. time, distances, frequency) without examining "how" (e. g. type of trajectory or starting position) and "why" (e. g. tactical role) soccer players sprint. In fact, other high-intensity actions, apart from running, are not even mentioned (i. e. curve sprints, change of direction, and specific-jump tasks). This has led to the use of tests and interventions that do not accurately reflect real game actions. Given the true technical-tactical-physical demands of each playing position, this narrative review collected a wide-spectrum of current soccer-related articles and provided a discussion regarding high-intensity actions, with a positional-based approach. In this narrative review, practitioners are encouraged to contemplate and consider the different elements that characterize high-intensity actions in soccer, in order to assess and train soccer players under a more sport-specific and integrative perspective.